Evaluation of critical factors determining the profitability of sweet maize - Kovács, Evelin (Acta Agraria Debreceniensis, 2016)
The main goal of this analysis was to determine, whether the production of sweet corn competitive is from the point of view of profitability and identify the main factors determining profitability. The hypothesis of this research was that sweet corn production is profitable and output factors (yields, selling prices) affect most significantly the profitability. The total costs of production with irrigation are 560 000 HUF ha-1. Average yield is 18 t ha-1, while selling prices on average of the last 5 years were about 38 000 HUF t-1. The realisable profit in the sector was 248 828 HUF ha-1. Direct cost-related profitability was 48.6% and profit level 26%. Elasticity analysis pointed out that the changes of selling prices and yields affect profitability. The critical value shows the turning point of profitability, which was at the yield of 13.82 t ha-1. It can be concluded, the hypothesis was true, because sweet corn production was profitable compared to other field crops.